2017
DOI: 10.1140/epjd/e2016-70347-6
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of Rb atoms in paraffin-coated resonant vapor cells

Abstract: Abstract. We present the results of a study of the diffusion of Rb atoms in paraffin -coated resonant vapor cells. We have modeled the Rb diffusion both in the cell and in the coating, assuming that the main loss of Rb atoms is due to the physical absorption of the atoms by the glass substrate. It is demonstrated that the equilibrium atomic density in the cell is a monotonic function of the thickness of the paraffin coating: the density increases with an increase in the thickness of the coating. The diffusion … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The value of the diffusion coefficient measured is equal within an error bar to the paraffin diffusion coefficient 5 × 10 −7 cm 2 /s that was measured in Ref. [13] and to the paraffin (n-Octadecane) self-diffusion coefficient 4.6 × 10 −7 cm 2 /s that was measured in reference [19].…”
Section: Methodssupporting
confidence: 62%
See 2 more Smart Citations
“…The value of the diffusion coefficient measured is equal within an error bar to the paraffin diffusion coefficient 5 × 10 −7 cm 2 /s that was measured in Ref. [13] and to the paraffin (n-Octadecane) self-diffusion coefficient 4.6 × 10 −7 cm 2 /s that was measured in reference [19].…”
Section: Methodssupporting
confidence: 62%
“…Then the atoms, after many bounces in the cell, start to diffuse deep inside the coating towards the glass substrate surface, where they are irreversibly absorbed. Not that, it takes rather long time to collect several equilibrium mono-layers of atoms on the glass substrate and obtain truly steady-state atomic density in common resonant cells [13,16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the incoherent part will depend on motion and wall collisions. It has been shown that even in the paraffin-or alkene-coated cells [34][35][36][37] or cells with dilute buffer gas [38] the atomic motion can be effectively described by the diffusion equation with adequate wall boundary condition. The cells with coated walls will feature a slow decay for the flat mode (𝑢 0 (x 𝑖 ) = 1/ √ 𝑉) which depends on intrinsic dynamics and wall decay, and much faster decay for all other modes, which given by 𝛾 𝑛 S = 𝐷 𝑘 2 𝑛 , where 𝐷 is the effective diffusion constant and 𝑘 𝑛 is the characteristic wavenumber of 𝑛-th mode [22].…”
Section: Theorymentioning
confidence: 99%